Homogeneity Index: An objective tool for assessment of conformal radiation treatments - Kataria, Tejinder (Medknow Publications & Media Pvt Ltd, 2012)
Homogeneity Index (HI) is an objective tool to analyz the uniformity of dose distribution in the target volume. Various formulae have been described in literature for its calculation but there is paucity of data regarding the ideal formula and the factors affecting this index. This study was undertaken to analyze HI in our patients using various formulae and to find out the co-relation between HI and prescribed dose, target volume and target location. A retrospective review of 99 patients was performed. HI was calculated using five different formulae (A-E). The patients were divided in five groups each, based on prescribed dose, target volume and target location and mean HI of each group was analysed to find the co-relation between these factors and HI. When there were multiple target volumes the primary target volume was studied. The statistical calculation was done using SPSS version 16.0. Ninety nine patients were found evaluable with 75 males and 24 females. Ninety five patients were treated with radical intent and four with palliative intent. The sites treated were head and neck (46.4%), Pelvis (17.1%), brain (15.1%), abdomen (12.1%), and thorax (6.1%). The mean prescribed dose was 4304 cGy (centiGray) and the mean target volume was 476.2 cc. The mean value of HI was 1.21, 2.08, 30.13, 21.51 and 1.27 with different formulae. There was considerable agreement between HI calculated using various formulae specially the formulae considering prescribed dose (C, D). On statistical analysis, there was no significant co-relation between the location and volume of target but there was a trend toward better HI with increasing prescribed dose. Future studies with more number of patients can confirm our results.